Eating Habits and Physical Condition of Physical Education Students [Hábitos Alimentarios y Condición Física en Estudiantes de Pedagogía en Educación Física] - Herrera-Valenzuela, T (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2014)
Objective: To determinate dietary habits and physical condition of physical activity students from the Autonomous University of Chile, Temuco, relating these to their fitness level. Methods: An observational cross-sectional study was conducted among 239 students (76.5 % males). Assessment included a food questionnaire, anthropometric measurements and physical condition. Results: In a sample of 239 students, 35.6% of them were overweight or obese as well as having unhealthy dietary habits independent of the academic year at university. Only 4.7 % of the students used the national recommendations for fruit intake and only 30% ate breakfast daily. In men weight, waist circumference and BMI were negatively associated with the Nvette Course test (R = -0.203, R= -0.249 and R= -0.196, p<0.01respectively). Conclusion: Physical activity education students have poor dietary habits throughout the university academic years while their fitness decreases irregularly as studies progress. This is a major concern since they will become healthy life style role models for their future students. © 2014 Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All rights reserved.